2017
DOI: 10.1371/journal.pone.0180351
|View full text |Cite
|
Sign up to set email alerts
|

A novel role of Krüppel-like factor 4 in Zhikong scallop Chlamys farreri during spermatogenesis

Abstract: Krüppel-like factor 4 (KLF4) is a kind of zinc finger transcription factor, which is involved in terminal differentiation of epithelial cells and reprogramming of somatic cells to induced pluripotent stem (iPS) cells in mammals. In the present study, we identified a full-length cDNA of Klf4 in Zhikong scallop Chamys farreri (Cf-Klf4) and found that Cf-Klf4 presented a sexual dimorphic expression characteristic in C. farreri gonads. Cf-Klf4 expression was significantly higher in testes than in ovaries from grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…RNA interference (RNAi), however, provides an alternative approach because of the direct injection of plasmids or RNAs. Moreover, compared to mammals, the effects of RNAi last much longer and it has been used in non-model invertebrate species, such as sea cucumber ( Apostichopus japonicus ) [21], Zhikong scallop ( Chlamys farreri ) [22], and Giant Freshwater Prawn ( Macrobrachium rosenbergii ) [23].…”
Section: Introductionmentioning
confidence: 99%
“…RNA interference (RNAi), however, provides an alternative approach because of the direct injection of plasmids or RNAs. Moreover, compared to mammals, the effects of RNAi last much longer and it has been used in non-model invertebrate species, such as sea cucumber ( Apostichopus japonicus ) [21], Zhikong scallop ( Chlamys farreri ) [22], and Giant Freshwater Prawn ( Macrobrachium rosenbergii ) [23].…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, a zinc nger transcription factor, known as kruppel-like factor 4 (KLF4), plays an important role in reprogramming of somatic cells to induced pluripotent stem cells. KLF4 has been reported to regulate early spermatogenesis and maintain the functions of testis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study of KLF4 gene in C . farreri indicated that Cf-KLF4 regulates early spermatogenesis, and promotes the differentiation of spermatogonia and spermatocyte, as well as the apoptosis of spermatocytes 23 . And our further transcriptomic study after Cf-KLF4 was knockdown showed that several genes exhibited similar expression patterns ( IAPs , TNFR , TRAF etc.)…”
Section: Discussionmentioning
confidence: 99%
“…69 and Yang et al . 23 with some modifications. Two specific primers, RNAi-F: 5′- TAATACGACTCACTATAGGGAG AGGACAAATACGCTCTACCAGG-3′ (T7 promoter underlined) and RNAi-R: 5′- TAATACGACTCACTATAGGGAG CATATGAGTAAGCGGAACAG-3′ (T7 promoter underlined) were designed according to Cf-SOX2 cDNA sequence to amplify a fragment of 506 bp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation